2017
DOI: 10.1038/srep41238
|View full text |Cite|
|
Sign up to set email alerts
|

Patient-specific hepatocyte-like cells derived from induced pluripotent stem cells model pazopanib-mediated hepatotoxicity

Abstract: Idiosyncratic drug-induced hepatotoxicity is a major cause of liver damage and drug pipeline failure, and is difficult to study as patient-specific features are not readily incorporated in traditional hepatotoxicity testing approaches using population pooled cell sources. Here we demonstrate the use of patient-specific hepatocyte-like cells (HLCs) derived from induced pluripotent stem cells for modeling idiosyncratic hepatotoxicity to pazopanib (PZ), a tyrosine kinase inhibitor drug associated with significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 69 publications
(85 reference statements)
1
31
0
Order By: Relevance
“…However, combination with low-dose doxorubicin resensitized the cells for apoptosis resulting in a synergistic cytotoxicity and inhibition of colony formation. A recent study (although not in the context of YAP signaling) also observed that pazopanib induced a shift toward a pro-oxidative state in induced pluripotent stem cells (45).…”
Section: Discussionmentioning
confidence: 92%
“…However, combination with low-dose doxorubicin resensitized the cells for apoptosis resulting in a synergistic cytotoxicity and inhibition of colony formation. A recent study (although not in the context of YAP signaling) also observed that pazopanib induced a shift toward a pro-oxidative state in induced pluripotent stem cells (45).…”
Section: Discussionmentioning
confidence: 92%
“…Metabolism studies must be more deeply explored, beyond the most abundant metabolites and considering even minor metabolites to be significant since their chemical structure and reactivity may well be risk factors in toxicity/DDI. Fortunately, advances have recently been made in this field, including in silico (theoretical chemistry and pharmacokinetic modeling) and in vitro (patient‐specific hepatocyte like cells derived from induced pluripotent stem cells, multicellular models) techniques. In addition, several in vivo models (CYP3a‐null, Por‐null mice [knockout of CYP or NADPH‐P450 oxidoreductase] or transgenic CYP‐ and liver‐humanized mice) have been developed as useful tools to identify the specific enzymes contributing to toxicity and to better extrapolate RM involvement in toxicity from mouse to human …”
Section: Discussionmentioning
confidence: 99%
“…Metabolism studies must be more deeply explored, beyond the most abundant metabolites and considering even minor metabolites to be significant since their chemical structure and reactivity may well be risk factors in toxicity/ DDI. Fortunately, advances have recently been made in this field, including in silico (theoretical chemistry and pharmacokinetic modeling) 38,155 and in vitro (patient-specific hepatocyte like cells derived from induced pluripotent stem cells, multicellular models) 31,140 techniques. In addition, several in vivo models (CYP3a-null,…”
mentioning
confidence: 99%
“…Choudhury et al showed the use of patient-specific iPS-Heps for modeling idiosyncratic hepatotoxicity to a tyrosine kinase inhibitor drug (Pazopanib) associated with significant hepatotoxicity of unknown mechanistic basis. Pazopanib caused disruption of iron metabolism and increased oxidative stress in iPS-Heps derived from patients compared with those derived from normal individuals [57]. A recent study showed that a cell sheet composed of human iPS-Heps expresses albumin, CYP3A4 and CYP1A2 at a comparable level to primary human hepatocytes [58].…”
Section: Disease Models Of Drug-induced Liver Injury and Autoimmune Hmentioning
confidence: 99%